Manejo de las complicaciones gineco obstétricas durante el embarazo y puerperio en adolescentes - Lopez Alvarado, Jandry Israel (Machala : Universidad Técnica de Machala, 2024)
Adolescent pregnancy is considered a public health problem due to the various maternal and fetal complications. Worldwide, 16 million cases of pregnant adolescents are reported. Objectives: 1. Define the therapeutic management of gynecological-obstetric complications during adolescent pregnancy and puerperium through a review of scientific articles. 2. To identify the most prevalent prenatal, perinatal and postnatal complications of adolescent pregnancy. 3. To establish recommendations for the management of adolescent pregnancy in primary care. Methods: Descriptive study, reviewing documents in different databases Pubmed, Medscape, EBSCOhost, Google Academic and Elsevier from the last five years. Conclusions: Within the management of hypertensive disorders of pregnancy, the use of nifedipine is mainly recommended. In ectopic pregnancy, methotrexate is used based on clinical criteria, and in case of failure to meet them, the treatment of choice is salpingectomy. Misoprostol is the most commonly used alternative for abortion. In gestational anemia, management with iron plus folic acid is recommended. In premature rupture of membranes, expectant management is expected in pregnancies of less than 34 weeks, and in pregnancies of more than 34 weeks, induction of labor is expected. In situations such as cephalopelvic disproportion the only option is cesarean section.
El embarazo adolescente se considera un problema de salud pública por las diversas complicaciones maternas y fetales. A nivel mundial se reportan 16 millones de casos de adolescentes embarazadas. Objetivos: 1. Definir el manejo terapéutico de las complicaciones gineco – obstétricas durante el embarazo y puerperio del adolescente mediante revisión de artículos científicos 2. Identificar las complicaciones prenatales, perinatales y post natales más prevalentes del embarazo adolescente. 3. Establecer recomendaciones del manejo en atención primaria del embarazo adolescente. Métodos: Estudio descriptivo, de revisión documentos en diferentes bases de datos Pubmed, Medscape, EBSCOhost, Google Academic y Elsevier de los últimos cinco años. Conclusiones: Dentro del manejo de los trastornos hipertensivos del embarazo se recomienda principalmente el uso del nifedipino. En el embarazo ectópico se utiliza el metrotexate en base a criterios clínicos y en caso de no cumplirlos el tratamiento de elección es la salpingectomía. El misoprostol es la alternativa más utilizada en el aborto. En la anemia gestacional se recomienda el manejo con hierro más ácido fólico. En la ruptura prematura de membranas en el caso de embarazos menores de 34 semanas se espera un manejo expectante y en los mayores de 34 semanas la inducción del parto. En situaciones como la desproporción cefalopélvica la única opción es la cesárea.
Keywords: MANEJO; COMPLICACIONES; EMBARAZO; ADOLESCENTES